Kurikulum Berbasis Kearifan Lokal dalam Membentuk Karakter Peserta Didik - Sandi Kurniawan; Halim (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2022)
This study aims to determine what kind of curriculum is based on local wisdom in shaping the character of students. This study uses an approach with data collection techniques in the form of literature studies. The data used by the author comes from the literature that is relevant to the problem. The data that has been obtained from the literature study are then selected according to the need to solve the existing problems, while the data analysis in this scientific paper is carried out descriptively. From the results of the study, it was found that the values ​​of local wisdom require a strategic function for the formation of national character and identity. A curriculum based on local wisdom that cares about it will lead to the emergence of an independent attitude, full of initiative, polite and creative. Building the character of students in schools through a local wisdom-based curriculum that contains values ​​that are relevant and useful for education. A curriculum based on local wisdom can be done by revitalizing local culture.